Family facing its most critical time. Questionable aspects of its dysfunctionality and the origin of perversion. - Alcalde Muñoz, Elvis Jorge (2016)
This paper provides an overview of the institution of family, its dysfunctionality, and aspects related to the deviant behavior phenomenon while emphasizing on the role of the State in drafting punitive and preventive policies. On the other hand, the paper aims to promote a true mechanism for preventive social policies regarding family as the nucleus of society and as the main driver of change in our criminogenic context.